2012
DOI: 10.1007/s00128-012-0535-9
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition and In Vitro Cytotoxic, Genotoxic Effects of Essential Oil from Urtica dioica L.

Abstract: The aim of this study was to determine the chemical composition of Urtica dioica essential oil, and to evaluate its cytotoxic and genotoxic effects, using cytogenetic tests such as the cytokinesis-block micronucleus assay and chromosomal aberration analysis in human lymphocyte cultures in vitro. GC-MS analysis of U. dioica essential oil identified 43 compounds, representing 95.8% of the oil. GC and GC-MS analysis of the essential oil of U. dioica revealed that carvacrol (38.2%), carvone (9.0%), naphthalene (8.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 22 publications
0
41
0
2
Order By: Relevance
“…Previously conducted studies showed that stinging nettle contains wide diversity of biologically active compounds. There are essential oils and terpenoids as the main components [9,10], carotenoids [4,9,11], fatty acids [9,11,12], different phenolic and polyphenolic compounds [1,3,9,13,14], essential amino acids, chlorophyll, vitamin C, vitamin K, vitamins of B series, tannins, carbohydrates, sterols, polysaccharides, isolectins [4,9,11,15], and minerals [9,16,17]. The most important carotenoids are β-carotene, neoxanthin, lycopene, and lutein [11]; fatty acids are palmitic and cis-9,12 linoleic and α-linolenic acids [9,11,12], while iron has been marked as the most important mineral [9].…”
Section: Introductionmentioning
confidence: 99%
“…Previously conducted studies showed that stinging nettle contains wide diversity of biologically active compounds. There are essential oils and terpenoids as the main components [9,10], carotenoids [4,9,11], fatty acids [9,11,12], different phenolic and polyphenolic compounds [1,3,9,13,14], essential amino acids, chlorophyll, vitamin C, vitamin K, vitamins of B series, tannins, carbohydrates, sterols, polysaccharides, isolectins [4,9,11,15], and minerals [9,16,17]. The most important carotenoids are β-carotene, neoxanthin, lycopene, and lutein [11]; fatty acids are palmitic and cis-9,12 linoleic and α-linolenic acids [9,11,12], while iron has been marked as the most important mineral [9].…”
Section: Introductionmentioning
confidence: 99%
“…С использованием CBMN изучались эффекты воздействия эфирного масла крапивы двудомной Urtica dioica на лимфоциты крови человека. Была выявлена значимая положительная корреляция между концентрацией эфирного масла, вносимого в культуру, и частотой микроядер, хромосомных аберраций, частотой клеток в апоптозе или некрозе [30]. Показано, что ванильная кислота в дозе 1 мг/мл значимо снижала частоту клеток с микроядрами, а в высокой дозе -2 мг/мл проявляла уже генотоксический эффект на ДНК [15].…”
Section: исследования генотоксических эффектов новых перспективных прunclassified
“…It is known for its application in folk medicine, where it has been used for the treatment of various diseases and disorders [1,2]. Recent studies have shown the presence of different classes of compounds, e.g., terpenoids [3,4], carotenoids [3,5,6], fatty acids [2,3,[6][7][8], phenolic, and polyphenolic compounds [1,3,[9][10][11], amino acids, chlorophyll, vitamin C, vitamin K, vitamins B series, tannins, carbohydrates, sterols, polysaccharides, isolectins [1,3,5,12], as well as minerals [3,13,14]. It is worth mentioning that stinging nettle is very rich in iron (leaves contain about 150 mg/kg), while some important fatty acids, e.g., palmitic, cis-9,12 linoleic and a-linolenic acids, are also detected [3].…”
Section: Introductionmentioning
confidence: 99%